Ash dieback survey - Pawsey, R (Commenwealth Forestry Institute, University of Oxford, 1983)
Details are given of the results of a survey of ash dieback carried out in the east-central region of England, from Humberside southward to Buckinghamshire. Ash dieback was prevalent throughout the area, the incidence of the disease being highest in Northamptonshire and adjacent areas in neighbouring counties, where the occurrence of dieback on ash trees over 25 ft in height was frequently over 40%. General observations made during the main survey, and the results of two other special surveys, indicated cl early that the incidence of ash dieback is related to the intensity of agricultural activity, particularly in areas of arable farming. The incidence of ash dieback recorded in the two special surveys was approximately eight times higher on trees in the agricultural countryside as compared with those in towns and villages.